2013
DOI: 10.1016/j.oraloncology.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular etiology of second primary tumors in contralateral tonsils of human papillomavirus-associated index tonsillar carcinomas

Abstract: Objectives For patients with tobacco-related head and neck squamous cell carcinoma (HNSCC), the occurrence of a second primary tumor (SPT) is an ominous development that is attributed to a field cancerization effect and portends a poor clinical outcome. The goal of this study was to determine whether patients with human papillomavirus (HPV)-related index tonsillar carcinomas can also develop SPTs in the contralateral tonsil, and to discern the molecular etiology of HPV-related tumor multifocality. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 21 publications
(17 reference statements)
2
60
0
2
Order By: Relevance
“…The occurrence of second HPV16-positive primaries, both in the tongue base and nasopharynx (EBV-negative) in this study is intriguing. Second HPV-associated cancers in the tonsils and nasopharynx and HPV-positive/EBV-negative nasopharyngeal carcinomas have previously been reported [22-24] and it is possible that the lymphoid tissue throughout Waldeyer’s ring is particularly susceptible to HPV-induced transformation. Second primaries occurring in patients with a history of HPV-positive OPC should be tested for HPV and further studies to investigate the frequency and timing of HPV-positive second H&N primaries are required to inform future follow-up protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of second HPV16-positive primaries, both in the tongue base and nasopharynx (EBV-negative) in this study is intriguing. Second HPV-associated cancers in the tonsils and nasopharynx and HPV-positive/EBV-negative nasopharyngeal carcinomas have previously been reported [22-24] and it is possible that the lymphoid tissue throughout Waldeyer’s ring is particularly susceptible to HPV-induced transformation. Second primaries occurring in patients with a history of HPV-positive OPC should be tested for HPV and further studies to investigate the frequency and timing of HPV-positive second H&N primaries are required to inform future follow-up protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described patients diagnosed with HPV-HNSCCs who subsequently developed SPTs of the head and neck; however, the SPTs in these reports developed in the tonsils or nasopharynx [7][8][9]. Our review of the literature suggests that this is the first report of synchronous HPV-positive SCCs of the bilateral BOT.…”
Section: Discussionmentioning
confidence: 66%
“…The incidence of second primary HPV-associated carcinoma is currently unknown. Joseph et al [8] reported an incidence of 4% for SPTs in the contralateral tonsil of patients presenting with an index HPV-associated tonsillar carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations